Role of electron transfer processes in the oxidation of aryl sulfides catalyzed by nonheme iron complexes. (1st February 2017) - Barbieri, Alessia; Di Stefano, Stefano; Lanzalunga, Osvaldo; Lapi, Andrea; Mazzonna, Marco; Olivo, Giorgio
ABSTRACT: The oxidation of a series of aryl 1-methyl-1-phenylethyl sulfides with H2 O2 catalyzed by the two tetradentate nonheme-iron complexes [(PDP)Fe II (SbF6 )2 ] and [(BPMCN)Fe II (OTf)2 ] occurs by an electron transfer-oxygen transfer (ET/OT) mechanism as supported by the observation of products deriving from fragmentation of the corresponding radical cations in association with S-oxidation products (sulfoxides). GRAPHICAL ABSTRACT: